Analisis Dugaan Praktik Kartel Bunga oleh Pelaku Usaha Pinjaman Online di Indonesia - Gunawan, Lauren Angel; Yap, Celine Alexia (Anthology: Inside Intellectual Property Rights, 2025)
The phenomenon of the high use of technology-based loans is one of the things that needs attention. The high level of usage must be accompanied by adequate supervision. One form of supervision can be carried out through aspects of business competition in the online lending industry. Recently, the Competition Supervisory Commission as the supervisory body for business competition has found that 97 companies in the online lending industry have set loan interest rates that exceed the regulated interest rates, which if this is proven, then the business actors have violated Article 5 of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. The research method used in writing this article is a normative research method, with data collected from laws and regulations to reports from media coverage. The results show that the allegations against online lending platforms are less relevant, but investigations by KPPU in following up on the potential for unfair business competition practices still need to be carried out to uphold justice in providing certainty for the public.